Orbital Signaling in Graves’ Orbitopathy - Draman, Mohd Shazli; Zhang, Lei; Dayan, Colin; Ludgate, Marian (Frontiers in Endocrinology, 2021)
Graves’ orbitopathy (GO) is a complex and poorly understood disease in which extensive remodelling of orbital tissue is dominated by adipogenesis and hyaluronan production. The resulting proptosis is disfiguring and underpins the majority of GO signs and symptoms. While there is a strong evidence for the thyrotropin receptor (TSHR) being a thyroid/orbit shared autoantigen, the insulin-like growth factor 1 receptor (IGF1R) is also likely to play a key role in the disease. Large progress has been made in understanding some aspects of the pathogenesis GO. This is mainly derived using in vitro and ex vivo analysis of the orbital tissues. Here, we have summarized the aspects of GO pathogenesis involving target autoantigens and their signalling pathways.